2013
DOI: 10.1002/pam.21717
|View full text |Cite
|
Sign up to set email alerts
|

Collection of Delinquent Fines: An Adaptive Randomized Trial to Assess the Effectiveness of Alternative Text Messages

Abstract: The collection of delinquent fines is a vast and ongoing public administration challenge. In the United Kingdom, unpaid fines amount to more than 500 million pounds. Managing noncompliant accounts and dispatching bailiffs to collect fines in person is costly. This paper reports the results of a large randomized controlled trial, led by the UK Cabinet Office's Behavioural Insights Team, which was designed to test the effectiveness of mobile phone text messaging as an alternative method of inducing people to pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 22 publications
3
65
0
Order By: Relevance
“…IDB (2011) surveys that literature as well as the use of new information technologies on individual behavior in several other policy areas, such as banking, and health. Haynes et al (2013) show the effect of text messages on the payments of delinquent fines. Kessler and Zhang (2014) summarize the differential effects of methods in the health literature.…”
Section: Introductionmentioning
confidence: 99%
“…IDB (2011) surveys that literature as well as the use of new information technologies on individual behavior in several other policy areas, such as banking, and health. Haynes et al (2013) show the effect of text messages on the payments of delinquent fines. Kessler and Zhang (2014) summarize the differential effects of methods in the health literature.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research conducted in the form of RCTs showed that the text message approach could be effective. These studies were done in both the medical world (Taylor et al 2012) (Youssef et al 2014) (Robotham et al 2016) and with defendants when it came to changing their behaviour in fine payments (Haynes et al 2013). This fine payment trial in particular demonstrates that defendants can be influenced by such an approach.…”
Section: Results In Context Of Previous Researchmentioning
confidence: 99%
“…Some find that the customisation of a message is a good way to get a recipient's attention (Dijkstra 2005). This can include using the person's name, which produced statistically significant results in the court service trial which increased fine payment, referred to previously (Haynes et al 2013). A standard reminder provided an increase of average fine payment of £4.16 (p = 0.034).…”
Section: Prior Studies Of Bnudging^by Sms Text Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, we draw on evidence from behavioural science 31 which suggests that email would be an effective mechanism by which EV owners could be prompted to switch electricity tariff. First, evidence suggests that EV owners will be more responsive to prompts delivered shortly after purchasing their EV, before they have developed strong habits over the timing of their charging 13,14,32 .…”
Section: Nudge: Going Beyond Opt-out Enrolmentmentioning
confidence: 99%